Curriculum Accommodations For Children Intellectual Disabilities in Madrasah Ibtidaiyah - Rahayu, Norma Anis; Junaidi, Ahsan Romadlon; Susilawati, Sinta Yuni (Department of Special Education, 2023)
Intellectual disability is a disorder characterized by significant limitations in intellectual function and adaptive behavior. Children with intellectual disabilities still have the right to receive educational services at special schools or inclusive schools or madrasas. The aim of this research is to describe curriculum accommodations for children with intellectual disabilities at Madrasah Ibtidaiyah. The curriculum accommodation referred to is the process of adjusting graduate competency standards, content standards, process standards and assessment standards. This research uses a qualitative approach with a case study strategy. Research findings show that madrasas accommodate curriculum at three different levels, including (1) using the pure 2013 curriculum, (2) using the 2013 curriculum with modified learning indicators, and (3) using an adaptive curriculum. These three levels are also implemented in content standards, process standards and assessment standards. So it can be concluded that curriculum accommodations for children with disabilities at madrasah ibtidaiyah are developed based on the child's abilities, needs and conditions